Low-temperature titania coatings for aluminium corrosion protection. (2nd January 2018) - Mori, Stefano; Lamastra, Francesca Romana; Kaciulis, Saulius; Soltani, Peiman; Montesperelli, Giampiero
ABSTRACT: TiO2 coatings on AA6082 aluminium alloy were obtained at low temperature (80 and 100°C) by the sol–gel dip-coating technique starting from titanium tetra-isopropoxide solution in ethyl alcohol. The preparation was carried out in the presence of acetic acid with both functions of catalyst and chelating agent. The curing temperatures used for these coatings are between 80 and 100°C, low enough to make such coatings suitable to incorporate additives such as organic inhibitors or polymeric nanoparticles. The coated samples were characterised by scanning electron microscopy and energy-dispersive spectroscopy, atomic force microscopy, X-ray diffraction, X-ray photoelectron spectroscopy and electrochemical impedance spectroscopy (EIS). Compact coatings with a thickness of 500 nm, consisting of amorphous and nearly stoichiometric titanium dioxide, were obtained. EIS results revealed an effective corrosion protection of the substrate for more than 120 h of immersion in 3.5 wt-% NaCl aqueous solution.